(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The concept of leadership plays an essential role in the functioning of schools. Formaleducation provided by schools requires stature, quality supporting workforce, trained competentacademic staff, above all capable instructional administrator. The research in this area has primarilyfocused on leadership and school effectiveness in terms of its academic achievement. The main premiseof the article is that school factors of effectiveness basically depend upon different styles of leadershipbeing adopted by the head teachers with reference to gender and type of the institutions public andprivate sector. To be familiar with the meanings of ‘effectiveness’ a number of terms and concepts isundergone frequently including ―competent, development, quality, improvement, evaluation, monitoring,reviewing, skilled, appropriateness, accountability, and performance.